Technological Development and Application of Photo and Video Theodolites - Rinaldo Paar; Miodrag Roić; Ante Marendić; Stjepan Miletić (Applied Sciences, 2021)
Theodolites are fundamental geodetic measuring instruments for all practical geodetic tasks, as well as for experimental geodetic scientific purposes. Their development has a long history. Photo and video theodolites represent the advanced development of classic theodolites. Development started in 19th century, but only in the last 15 years has commercial application been achieved in the geodetic profession. The latest development, called image-assisted total stations (IATS), is a theodolite which consists of a classic robotic total station (RTS) with integrated image sensors. It was introduced in the early 2000s. With the development of theodolites, their application became much wider; today, they can be used for structural and geo-monitoring, i.e., for the determination of static and dynamic displacements and deformations of civil engineering structures such as bridges, dams, wind turbines, and high buildings, as well as natural structures, such as mountain slopes. They can be implemented in geodetic monitoring systems, which are an integral part of engineering structural diagnosis, and they provide essential information about the current condition of the structure. This paper describes the technological development of photo and video theodolites divided into phases according to the main innovations in their development. The application of modern video theodolites (i.e., IATS) is presented through several experimental studies that were performed. The procedure of conducting measurements with this kind of instrument, as well as the analysis of acquired data and achieved results, is elaborated. Lastly, the authors conclude, according to the achieved results, that IATS can today be used for determination of quasi-static and dynamic displacements with small and high amplitudes.